2019
DOI: 10.3892/ijo.2019.4755
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus infection and ocular surface disease (Review)

Abstract: Human papillomavirus (HPV) infection has been implicated as a primary cause of lesions in the anogenital region, skin, oropharynx and respiratory tract. Additionally, the role of HPV in the pathogenesis of ocular surface disease has also been extensively studied. Conjunctival papilloma development has been strongly associated with the HPV infection of certain subtypes. On the other hand, the role of HPV in conjunctival pterygium, conjunctival intraepithelial neoplasia (CIN) and ocular surface squamous neoplasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 91 publications
2
38
0
2
Order By: Relevance
“…Real-time PCR can eliminate the risk of carryover contamination. Our results showed no HPV DNA in the 116 pterygium swabs, consistent with nine studies that also showed no HPV DNA in pterygia using different HPV detection techniques 3 , 22 . Moreover, Tulvatana et al studied HPV prevalence in ocular surface squamous neoplasia in Thailand and found no HPV DNA 23 .…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Real-time PCR can eliminate the risk of carryover contamination. Our results showed no HPV DNA in the 116 pterygium swabs, consistent with nine studies that also showed no HPV DNA in pterygia using different HPV detection techniques 3 , 22 . Moreover, Tulvatana et al studied HPV prevalence in ocular surface squamous neoplasia in Thailand and found no HPV DNA 23 .…”
Section: Discussionsupporting
confidence: 92%
“…Many studies have found HPV DNA in pterygium samples using different techniques including PCR, Southern blotting, immunohistochemistry, in situ hybridization, and the Hybrid capture assay II. HPV prevalence varied among these studies, ranging from 0%–100%, and the strains of detected HPV DNA also differed among studies 3 , 20 . Thus, no consensus has been reached regarding HPV as a possible pathogenic cofactor.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations